2020
DOI: 10.1039/c9mh01191a
|View full text |Cite
|
Sign up to set email alerts
|

A nanolayer coating on polydimethylsiloxane surfaces enables a mechanistic study of bacterial adhesion influenced by material surface physicochemistry

Abstract: A 2 nm PDMS-like film coating allows identification of the influential factors on bacterial adhesion at the initial colonization stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 59 publications
(45 reference statements)
6
53
1
Order By: Relevance
“…For measuring the WCA on PEG, a thin layer of the liquid was applied to a glass slide. The values for PDMS and PEG correspond well with values known from literature [ 59 , 61 , 79 , 80 ]…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…For measuring the WCA on PEG, a thin layer of the liquid was applied to a glass slide. The values for PDMS and PEG correspond well with values known from literature [ 59 , 61 , 79 , 80 ]…”
Section: Resultssupporting
confidence: 86%
“…For measuring the WCA on PEG, a thin layer of the liquid was applied to a glass slide. The values for PDMS and PEG correspond well with values known from literature [59,61,79,80] Even if the applied plasma processes differ for the two types of samples, they are quite similar in the resulting surface properties concerning hydrophilicity. Again, the effect of draining duration on the successful attachment of PEG, as discussed earlier, becomes clearly apparent.…”
Section: Wca Measurementssupporting
confidence: 86%
“…Both high deposition rates (e.g., for water‐repellent coatings on textiles) and low deposition rates (e.g., for nm‐thick cover layers for diffusion control) were targeted. [ 35,75,76 ] Hence, varying deposition conditions over a broad range of power input, monomer gas flow rate, pressure, and plasma volume were applied. In the following, these results as well as literature data are revisited in light of the introduced formalism.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30,32,33 ] Recently, nm‐thick HMDSO‐derived PPFs have been applied as surface chemistry‐defining cover layers to gain new insights into protein and bacteria adhesion. [ 34,35 ] Noteworthy, water intrusion was found to affect biomolecule adsorption, whereas the mechanical properties of the substrate material appeared to be of less importance. Furthermore, HMDSO plasma‐modified hydrogels allow for the controlled release of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…24 Several studies have reported that the modulus of PDMS can be adjusted by altering the ratio of crosslinking. [29][30][31][32][33][34] However, as the ratio of crosslinking agent is reduced, the amount of un-crosslinked PDMS molecules is increased. Consequently, free molecules of silicone oils can migrate to the surface and cause various problems, such as increased adhesion between PDMS and substrate, 35 or formation of a phase-separated liquid meniscus.…”
Section: Introductionmentioning
confidence: 99%